Valuation, personal taxes, and dividend policy under passive debt management - Stefan Dierkes; Johannes Sümpelmann (Review of Quantitative Finance and Accounting, 2025)
We derive consistent valuation models in accordance with the flow to equity and adjusted present value approaches under passive debt management considering the firm's dividend policy and differentiated personal taxes at the equity investor level. The valuation models include a blended personal tax rate encapsulating all the effects resulting from retention and cash dividends. Furthermore, we establish appropriate adjustment formulas for the relationship between the firm's unlevered and levered cost of equity necessary for the unlevering and relevering of beta factors. Finally, we show with simulations that dividend policy significantly affects the equity market value.
Keywords: G32; H20; M41; 330; Valuation; Personal taxes; Passive debt management; Financing policy; Dividend policy; Share repurchases; Cost of equity; Simulations